Uji ketahanan fatik aluminium hasil remelting piston bekas menggunakan metode pengecoran centrifugal casting - Nugroho, Eko; Budiyanto, Eko; Kurniawan, Rubi; Sumosusilo, Joko (TURBO [Tulisan Riset Berbasis Online], 2019)
Aluminum is one of the non-ferrous metals that are most widely used in the engineering field due to it has mild properties and is resistant to corrosion, but aluminum waste such as used pistons that are damaged or not utilized as an proper resource, on the other hand, that this process is very potential due to it uses a used piston that is not used, and is expected to have a better economic value by doing remelting and centrifugal casting to the used piston. This study aims to determine the value of the fatigue cycle of the used piston which is remelting and printed using the centrifugal casting method by using variations in the pouring temperature and die temperature and rotation variations. Based on the tests conducted using pouring temperature variations and rotation speed are as follows: best cycle value at 250 rpm variation is at pouring temperature 600oC with a value of 76000 N, and the lowest is at room temperature of 750oC with a value of 32000 N, best cycle at a variation of 500 rpm is at a pouring temperature of 700oC with a value of 40000 N, and the lowest is at a room temperature of 660oC with a value of 12000 N. The best cycle value at a variation of 750 rpm is at a pouring temperature of 750oC with a value of 16000 N, and the lowest is at room temperature 660oC with a value of 10000 N. While the results of subsequent tests conducted using variations in die temperature and rotation speed are as follows: the best cycle value at 250 rpm variation is at a print temperature of 350oC with a value of 17400 N, and the lowest is at room temperature of 250oC with a value of 8370 N. The best cycle value at a variation of 500 rpm is at a print temperature of 350oC with a value of 67760 N, and the lowest is at a room temperature of 250oC with a value of 22850 N. The best cycle value at a variation of 750 rpm is at a print temperature of 350oC with a value of 75170oC. and the lowest is at room temperature of 250oC with a value of 28940 N.Keywords: Centrifugal casting, fatigue test, remelting, used piston, aluminum, cycle value.Barbarslot adalah salah satu situs resmi slot deposit 5000, 5rb dan depo 5k terbaru dengan beragam permainan terbaik tahun 2025.